How to boil water. (Stuttgart : Dr. Cantz'sche Druckerei, 1994)
Banke, Martin ; Brieske, Claudia ; Els, Tobias ; Koelner, Rebecca ; Kremer, Carsten ; Schmidt, Regina Florida
Documents some of the activities and projects realized or originated in 1992/1994 by students at HBK Saar during the tenure of Serge Spitzer as Professor of Sculpture
kunstcatalogus